Towards a Variegated Approach to Textual Fluidity: Limited Variations, Deliberate Duplication and a Creative Scribal Mistake in 2 Kings 10:15-31 - Richelle, Matthieu (Henoch, 2020)
The concept of textual fluidity, albeit most helpful to underline the existence of an important aspect of the textual history of the Hebrew Bible, does not enable us to assess its scope or its manifold manifestations. While it is often noted that some scribes were conservative and others were creative, this paper takes a passage in the Books of Kings as an illustration of the fact that the situation is still more complex than that. Even in the framework of the creative approach, various degrees of creativity should be distinguished. Similarly, in the framework of the conservative approach, inadvertant changes led to meaningful, creative rewriting. As a result, a variegated understanding to scribal activity is suggested. We should think in terms of a spectrum and go beyond the simple opposition between conservative and creative scribal approaches, to recognize that there were various shades of creative activity. Textual fluidity was itself a fluid phenomenon.